Unilateral fibrotic enlargement of gingiva with unknown etiology: A rare findings - Mohammad Arif Khan; Amitandra Kumar Tripathi; Rajeev Kumar Jaishwal; Poonam Agrawal (Wolters Kluwer Medknow Publications, 2015)
Idiopathic gingival enlargement is a rare condition characterized by massive enlargement of the gingiva. It can be an isolated entity or may be associated with syndrome. In this case report, A 15-year-old female reported with a chief complaint of swollen gums which was slowly progressive since last 2 years that affects the esthetic appearance and functional movement such as mastication. On her intraoral examination revealed that there was unilateral, generalized, diffuse fibrotic gingival enlargement with pseudopockets. The lesion was surgically removed. Postoperative healing was satisfactory with significant improvement in esthetic appearance and mastication. There was no postoperative recurrence during 2 years of follow-up.